Stereotactic Radiosurgery for Perioptic Meningiomas: An International, Multicenter Study - Bunevicius, Adomas; Anand, Rithika Kormath; Suleiman, Mohanad; Nabeel, Ahmed M; Reda, Wael A; Tawadros, Sameh R; Abdelkarim, Khaled; El-Shehaby, Amr M N; Emad, Reem M; Chytka, Tomas; Liscak, Roman; Sheehan, Kimball; et al. (Neurosurgery, 2021)
BACKGROUND: Stereotactic radiosurgery (SRS) is increasingly used for management of perioptic meningiomas. OBJECTIVE: To study the safety and effectiveness of SRS for perioptic meningiomas. METHODS: From 12 institutions participating in the International Radiosurgery Research Foundation (IRRF), we retrospectively assessed treatment parameters and outcomes following SRS for meningiomas located within 3 mm of the optic apparatus. RESULTS: A total of 438 patients (median age 51 yr) underwent SRS for histologically confirmed (29%) or radiologically suspected (71%) perioptic meningiomas. Median treatment volume was 8.01 cm3. Median prescription dose was 12 Gy, and median dose to the optic apparatus was 8.50 Gy. A total of 405 patients (93%) underwent single-fraction SRS and 33 patients (7%) underwent hypofractionated SRS. During median imaging follow-up of 55.6 mo (range: 3.15-239 mo), 33 (8%) patients experienced tumor progression. Actuarial 5-yr and 10-yr progression-free survival was 96% and 89%, respectively. Prescription dose of ≥12 Gy (HR: 0.310; 95% CI [0.141-0.679], P = .003) and single-fraction SRS (HR: 0.078; 95% CI [0.016-0.395], P = .002) were associated with improved tumor control. A total of 31 (10%) patients experienced visual decline, with actuarial 5-yr and 10-yr post-SRS visual decline rates of 9% and 21%, respectively. Maximum dose to the optic apparatus ≥10 Gy (HR = 2.370; 95% CI [1.086-5.172], P = .03) and tumor progression (HR = 4.340; 95% CI [2.070-9.097], P < .001) were independent predictors of post-SRS visual decline. CONCLUSION: SRS provides durable tumor control and quite acceptable rates of vision preservation in perioptic meningiomas. Margin dose of ≥12 Gy is associated with improved tumor control, while a dose to the optic apparatus of ≥10 Gy and tumor progression are associated with post-SRS visual decline.
Keywords: dospělí; Magnetic Resonance Imaging; Female; Perioptic meningioma; Visual outcomes; Adult; výsledek terapie; mladý dospělý; ženské pohlaví; Stereotactic radiosurgery; doba přežití bez progrese choroby; Meningeal Neoplasms; Adolescent; Gamma Knife; Internationality; lidé; Meningioma; magnetická rezonanční tomografie; internacionalita; meningeální nádory; Aged, 80 and over; následné studie; Treatment Outcome; radiochirurgie; retrospektivní studie; Radiosurgery; Follow-Up Studies; Male; Aged; Outcomes; Young Adult; nervus opticus; meningeom; Optic Nerve; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Progression-free survival; Retrospective Studies; Progression-Free Survival; Middle Aged; mladiství; Humans